Comparison of the effectiveness of beetroot juice (beta vulgaris l.) and date palm extract (phoenix dactylifera) on increasing hemoglobin levels among adolescent girls with anemia: A quasi-experimental study - Shindi Shafitri; Setiawati Setiawati; Umi Romayati Keswara (School of Health Sciences Al-Ma'arif, 2026)
Background: Anemia is a common health problem among adolescent girls and may reduce concentration, physical fitness, learning capacity, and future reproductive health. Beetroot juice and date palm extract are potential non-pharmacological nutritional interventions for increasing hemoglobin levels. However, comparative evidence between these two interventions among adolescent girls with anemia remains limited. Objective: This study aimed to compare the effectiveness of beetroot juice and date palm extract in increasing hemoglobin levels among adolescent girls with anemia at SMA Negeri 14 Bandar Lampung in 2026. Methods: This quantitative study used a quasi-experimental two-group pretest-posttest design and was reported in accordance with relevant TREND guideline items for non-randomized intervention studies. Thirty adolescent girls with anemia were selected through purposive sampling from 196 grade XI female students and allocated into two equal intervention groups. The beetroot juice group received 250 mL of beetroot juice once daily for seven consecutive days, while the date palm extract group received one tablespoon of date palm extract twice daily for seven consecutive days. Hemoglobin levels were measured before and after intervention using the EasyTouch GCHb device. Data were analyzed using the Wilcoxon signed-rank test, Mann-Whitney U test, and effect size estimation. Results: The mean hemoglobin level increased from 10.827 to 12.980 g/dL in the beetroot juice group, with a mean difference of 2.153 g/dL, and from 10.687 to 11.540 g/dL in the date palm extract group, with a mean difference of 0.853 g/dL. The Wilcoxon test showed significant increases in both groups (p = 0.001), with a large effect size in the beetroot juice group (r = 0.89) and date palm extract group (r = 0.89). The Mann-Whitney U test showed a significant difference in hemoglobin improvement between groups (p = 0.001), with a large between-group effect size (r = 0.68; Cliff’s delta = 0.80). Conclusion: Beetroot juice and date palm extract were associated with increased hemoglobin levels among adolescent girls with anemia, with a greater increase observed in the beetroot juice group. The interventions may be considered complementary food-based nutrition education strategies rather than substitutes for iron supplementation programs.